HONEYPOTS IN NETWORK SECURITY - Salimova Husniya Rustamovna (Galaxy International Interdisciplinary Research Journal, 2022)
Security issues become one of the important aspects of a network, especially a network security on the server. These problems underlie the need to build a system that can detect threats from parties who do not have access rights (hackers) that are by building a security system honeypot. A Honeypot is a diversion of intruders’ attention, in order for intruders to think that it has managed to break down and retrieve data from a network, when in fact the data is not important and the location is isolated. A way to trap or deny unauthorized use of effort in an information system. One type of honeypot is honeyd. Honeyd is a low interaction honeypot that has a smaller risk compared to high interaction types because the interaction with the honeypot does not directly involve the real system. The purpose of the implementation of honeypot and firewall, firewall is used on Mikrotik. Can be used as an administrative tool to view reports of Honeyd generated activity and administrators can also view reports that are stored in the logs in order to assist in determining network security policies.